Research on the impact of team reward interdependence on employees’ innovative behavior in enterprises: a cross-level moderated mediation model - Li, Xinchun; Wang, Zhi; Xu, Xianzhi (Frontiers in Psychology, 2026)
China currently insists on focusing its efforts on the real economy in developing the economy. Therefore, it is necessary to place technological innovation at the center of the overall enterprise’s development, and fully stimulate the innovative and creative talents of all kinds of talents. Based on the Social Interdependence Theory (SIT) and the Planned Behavior Theory (PBT), this study examines how team reward interdependence (TRI) of cross-level influences Innovative behavior, with innovation intention serving as a mediator and task interdependence acting as a contextual moderator. Through empirical analysis of two-time-point paired questionnaire survey data from 331 employees and their leaders, it is found that TRI has an indirect positive impact on innovative behavior (β = 0.369), and innovation intention plays a complete mediating role (β = 0.320). The analysis reveals that task interdependence not only positively moderates (β = 0.203) the relationship between team reward interdependence and innovation intention, but also further moderates (β = 0.200) the indirect effect of TRI on innovative behavior through innovation intention.